Opioid Use Is Reduced in Patients Treated with NSAIDs After Arthroscopic Bankart Repair: A Randomized Controlled Study - Kamali A. Thompson, B.S., M.B.A; David Klein, D.O; Michael J. Alaia, M.D; Eric J. Strauss, M.D; Laith M. Jazrawi, M.D; Kirk A. Campbell, M.D (Elsevier, 2021)
Purpose: To evaluate the efficacy of oral nonsteroidal anti-inflammatory drugs (NSAIDs) as the primary postoperative pain medication compared with standard oral opioids after arthroscopic shoulder capsulolabral (Bankart) repair for recurrent anterior shoulder instability. Methods: This was a single-center, prospective, randomized controlled study. Patients aged 18 to 65 years indicated for arthroscopic shoulder capsulolabral repair for recurrent anterior shoulder instability were included. Postoperatively, patients were prescribed 1 of 2 analgesic regimens: (1) 30 ibuprofen (600 mg every 6 to 8 hours as needed) and 10 tablets of oxycodone/acetaminophen (5/325 mg every 6 hours as needed for breakthrough pain) or (2) 30 tablets oxycodone/acetaminophen (5/325 mg every 6 hours as needed). Subjects completed questionnaires at 24, 48, and 96 hours and 1 week after surgery, which included questions about analgesic medication usage, visual analog scale (VAS) pain score, incidence of adverse events, and patient satisfaction. Results: Between December 2017 and May 2019, 80 patients (mean age 31.3 ± 10.4 years) were enrolled. Overall there were no significant differences in VAS pain score or patient satisfaction between the 2 groups. Patients in the opioid-only group had a significantly higher mean opioid consumption on postoperative days (PODs) 2 to 4 (5.5 versus 2.9, P = .05) and after 1 week (11.7 versus 7.9 tablets, P = .05) compared with patients in the NSAID group. Of patients in the NSAID group, 17.5% experienced adverse effects, compared with 35% in the opioid-only group. Conclusions: Use of oral NSAIDs with limited breakthrough opioids results in significantly less opioid use after arthroscopic Bankart repair in the first postoperative week compared with opioids only. Both groups used limited amounts of opioids to control postoperative pain. There were no differences in pain levels at any time point postoperatively or satisfaction between patient groups. Level of Evidence: II, nonblinded randomized control trial.